Agronomy, Utilization and Economics of Indigenous Vegetables in West Java, Indonesia - Edi Santosa; Utami Prawati; , Sobir; Yoko Mine; Nobuo Sugiyama (Jurnal Hortikultura Indonesia, 2015)
ABSTRACTIndigenous vegetables have become popular in recent Indonesian diet, but agronomic and economic studies on these crops are limited. The objective of this research was to investigate the cultural technique of indigenous vegetables, their uses and economic importance in West Java, Indonesia. Initial market observation was conducted in Bogor to determine the economic value of indigenous vegetables. In depth observations of the indigenous vegetables and interviews with merchants, farmers and consumers were conducted in three districts, i.e., Bogor, Cianjur and Tasikmalaya, focusing on four indigenous vegetables familiar to local people, i.e., genjer (Limnocharis flava (L.) Buchenau), kenikir (Cosmos caudatus Kunth.), leunca (Solanum americanum Miller) and poh-pohan (Pilea melastomoides (Poir.) Wedd.). This study showed that indigenous vegetables have been produced in extensive and semi-intensive cultivations and are sold in local markets daily, although local people do not consume them frequently. Indigenous vegetables held a market share of less than 5% at local markets, and accounted for less than 10% in household vegetable consumption. The reasons for consumers to choose indigenous vegetables were familiarity to these crops, moderate prices, family members’ preference, availability and ease of preparation. Generally, younger family members (<30 years old) bought indigenous vegetables less frequently than older ones (>30 years old), possibly due to lack of information on its use, unfamiliar flavor and high availability of other commercial vegetables commonly grown worldwide.Keywords: Cosmos caudatus, Limnocharis flava, local knowledge, Pilea melastomoides, Solanum americanumABSTRAKPopularitas sayuran indigenus terus meningkat di Indonesia, namun studi agronomi dan ekonominya masih terbatas. Penelitian bertujuan mengkaji budidaya, pemanfaatan dan nilai ekonomis sayuran indigenus di Jawa Barat, Indonesia. Penelitian pendahuluan dilakukan di pasar di wilayah Bogor. Penelitian mendalam dilakukan dengan mewawancarai pedagang, petani dan konsumen, serta mengamati di lahan petani di tiga kabupaten yakni Bogor, Cianjur dan Tasikmalayauntuk empat sayuran indigenus utama yakni genjer (Limnocharis flava (L.) Buchenau), kenikir (Cosmos caudatus Kunth.), leunca (Solanum americanum Miller) dan poh-pohan (Pilea melastomoides (Poir.) Wedd.). Studi menunjukkan bahwa sayuran indigenus diproduksi secara intensif dan semi intensif, serta dijual di pasar setiap hari, walaupun penduduk setempat tidak mengkonsumsi secara teratur. Sayuran indigenus mengisi celung pasar kurang dari 5% dan memenuhi kurang dari 10% kebutuhan sayuran rumah tangga. Konsumen memilih sayuran indigenus karena sudah terbiasa mengkonsumsi, harga terjangkau, disukai anggota keluarga,ketersediaan dan kemudahan mengolah. Secara umum, anggota keluarga muda (usia < 30 tahun) lebih jarang membeli sayuran indigenus dibanding yang lebih tua (usia > 30 tahun), kemungkinandisebabkan keterbatasan informasi nilai guna, adanya aroma asing, dan ketersediaan sayuran lain.Kata kunci: Cosmos caudatus, Limnocharis flava, pengetahuan lokal, Pilea melastomoides, Solanum americanum